ATP8B1 mutations in British cases with intrahepatic cholestasis of pregnancy. Issue 6 (11th May 2005) - Müllenbach, R; Bennett, A; Tetlow, N; Patel, N; Hamilton, G; Cheng, F; Chambers, J; Howard, R; Taylor-Robinson, S D; Williamson, C
Abstract : Background: Intrahepatic cholestasis of pregnancy (ICP) affects approximately 0.7% of pregnancies in the UK and is associated with prematurity, fetal distress, and intrauterine death. Homozygous mutations in the ATP8B1 gene cause cholestasis with a normal serum gamma-glutamyl transpeptidase (γ-GT), and have been reported in two forms of cholestasis: progressive familial intrahepatic cholestasis type 1 (PFIC1) and benign recurrent intrahepatic cholestasis (BRIC). Aims: To establish whether mutations in ATP8B1 are associated with ICP in British cases Patients: Sixteen well phenotyped women with ICP without raised γ-GT were selected for sequence analysis. Subsequently, 182 patients and 120 controls were examined for the presence of the variants detected. Methods: All coding exons were sequenced in 16 cases. Eight ICP cases, including two women carrying a mutation, were investigated using in vivo hepatic 31 P magnetic resonance spectroscopy (MRS) Results: Two heterozygous ATP8B1 transitions (208G>A and 2599C>T) that resulted in amino acid substitutions were identified; 208G>A was identified in three cases. MRS revealed an increased phosphodiester signal (Mann-Whitney U test, p = 0.03) and a decreased phosphomonoester/phosphodiester ratio (p = 0.04) in ICP cases compared with controls. Conclusions: We were able to demonstrate ATP8B1 mutations in ICP. MRS studies suggest that susceptibility to ICP is associated with a relative rise in biliary phospholipid. These data also suggest that MRS may be used for non-invasive assessment of the liver and biliary constituents in cholestasis.